Intermediate Role Of information Technology In The Relationship To The Entrepreneurial Orientation and Success Factors Of The Project (Analytical exploratory research in Al – Zawraa General Company) - محمدعلي شفاء محمد علي; عبد الامير علي حسين (Journal of Economics and Administrative Sciences, 2019)
The purpose of the current research is to identify the reality and applicability of the entrepreneurial approach in its dimensions (creative, proactive, independent, risk tolerant, offensive) and its impact on the success factors of the project (organizational commitment, communication, project team, project monitoring) Access to information, treatment, storage), which is a significant and important link in the success and development of industrial projects with the possibility of studying and analyzing the provision of the appropriate environment for this. the research started from a problem expressed by a number of intellectual and practical questions aimed at answering them as well as To answer a number of questions and the most important - What is the reality of the pioneering dimensions of orientation in the company surveyed? , What are the most important factors in the success of the project in the company investigated? . The objective of the research at the possibility of advancing the status of information technology in the company investigated, and make suggestions and recommendations to develop the role of the leading trend in achieving the success factors of the project. The research included (7) main hypotheses, which were at the total level and at the sub-dimensions level, which show the correlation and influence between the search variables and to achieve the hypothesis tests applied to the research sample (the solar cell project in Al-Zorra General Company) adopted the questionnaire as the main tool for collecting data and information through (125) members out of (195). A well as conducting interviews with some of the respondents in question, where he met (15) managers distributed on the sections of Wa For the people and administrative units in the project. The data were analyzed using SPSS and a number of statistical methods were used to process the data including: arithmetic mean, percentage, standard deviation, variance coefficient, path analysis method, And the use of correlation coefficient (Pearson) to test the validity of correlation hypotheses and the use of simple linear regression coefficient to study the effect between the basic variables. The researcher also reached a set of results that important project by information technology and the changes that are made to the dimensions of leadership orientation followed by this change in other variables.